The design and development of a multimedia program for graphs of trigonometric functions - Fabian, Maria Khristin A. (Animo Repository, 2007)
This thesis is a developmental research report on the design and development of a multimedia material for high school trigonometry. Carpenter and Lehrer's (1999) five forms of mental activity that promote mathematics was used as a guideline to develop the multimedia material. The multimedia material was designed and developed using the four-step multimedia development process of concept, design, production, and evaluation. The Concept Phase identified the learning difficulties of students and the topics covered in graphs of Trigonometric functions. The Design Phase incorporated the five forms of mental activity with the pedagogical designs of constructivism and the activity of Goal-based Scenario. The Production Phase entailed the development of the multimedia material using Macromedia Flash. During the Evaluation Phase, the program was evaluated in terms of technical design, navigation, and content. The positive responses of the teachers indicate that the program will be a valuable addition to the instruction of graphs of trigonometric functions. The students positive attitudes on the evaluation session, as evidenced by the fact that they explored the multimedia program willingly and inquisitively, indicate the favorable reception of the interactive software in the Mathematics classroom.